Factors that Influence Employee Job Performance: A Case Study of GDEX Express Carrier Bhd - Cha, Kian Teow; Zhang, Zihui; Tang, Yueheng (INTI International University, 2024)
The purpose of this study is to investigate the key factors influencing employee job performance in GDEX. Employee job performance has been found to be easily influenced by corporate behaviours. Therefore, it is important for an organisation to know pertinent issues that are capable of influencing employee job performance in order to help the organisation achieve high-quality work performance in future. The main objective of this study is to investigate variables that would influence employee job performance in GDEX. The four variables include training and development, rewards, good working environment, and effective communication toward employee job performance in GDEX. This study employed the qualitative approach to study employee job performance in a logistics company. The secondary data has been chosen as a research technique to analyze and examine the problem. Based on the secondary research, the findings showed that training and development, rewards, good working environment, and effective communication has a significant positive effect on employee job performance.